Indikasi Awal Aktivitas Maritim pada Lahan Basah di Pulau Kompei - Stanov Purnawibowo (Balai Arkeologi Sumatera Utara, 2008)
AbstractMaritim activities in Pulau Kompei and arround, can be indicated from archaeological reminds and wetland environment data. Although with a few archaeological and environmental data, early maritim activities can be indicated.